Experimental Investigation of the Dynamics of Laboratory Simple Surge Tank - Yousif, Saib A.; Kalaf, Ali Nasir (Basrah Journal for Engineering Sciences, 2017)
The surge tank is one of important control devices in reducing water Hummer effect on distributed network piping system and hydropower stations. An experimental study was conducted into a simple surge tank of 0.044 m in a diameter with upstream constant head reservoir of a height, 0.881 m and a water transporting pipe of a size 0.0202 m. Results indicate that rapid closure of a downstream valve causes under-damped stable oscillation in a surge tank. Experimental response agreed well with theoretical results when friction factor is considered to be variable, but with 85 % increases in settle time and more oscillations when constant friction factor is recognized at initial value before valve closure. Doubling surge tank area does not improve the dynamics properties; otherwise, Thoma area must be avoided for small sizes. Comsol multiphysics software 3.5 is used to deal with the dynamics of the surge tank numerically.